Critical velocity sensibility in young swimmers during a trainning macrocycle - Magalhaes Guedes, J.; Costa, A. P.; Soares Pereira, R. J.; da Silva, S. F. (Brazilian Journal of Biomotricity, 2011)
Several studies has been investigated the Critical Velocity (CV) is an indirect method to estimate the anaerobic threshold (AT). However, is lagged the literature to show the CV behavior during a training period. The aim of this study was to evaluate the sensitivity of CV in young swimmers during a training macrocycle. After it, we checked if the CV tests, could be used as a way to control training parameters. It were evaluated 8 swimmers at state / national level. To calculate the CV, the athletes swam distances of 100 and 200 meters in the possible shortest time. The CV was determined by the slope (b) of the linear regression line between the distances and the respective periods. To verify if the CV correlated with AT, it has been done three shots of 400 meters at the corresponding intensity to the time of Critical Velocity. The results showed no differences significant statistics among the three times of CV tests. We conclude that although there was no differences significant statistics among Critical Velocity time, when we compared the beginning tests with the final tests, we found a slope of 2.5 seconds in the CV time.